2018
DOI: 10.2147/jir.s152326
|View full text |Cite
|
Sign up to set email alerts
|

Early exposure to distinct sources of lipids affects differently the development and hepatic inflammatory profiles of 21-day-old rat offspring

Abstract: IntroductionMaternal diet composition of fatty acids during pregnancy and lactation seems to modify the fetal programming, epigenetic pattern and offspring phenotype.AimHerein, we investigated the effects of maternal consumption of normal-fat diets with distinct lipid sources during pregnancy and lactation on the somatic development and proinflammatory status of 21-day-old rat offspring.Materials and MethodsOn the first day of pregnancy, female Wistar rats were divided into four groups as follows: soybean oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…During the pregnancy and/or lactation period, diet represents one of the essential environmental factors that can have beneficial or adverse consequences on phenotype and health of offspring [1]. Evidence that the quantity but also the type of dietary fatty acids (FA) in maternal diet during this period could influence the fetal programming has emerged [3][4][5]. Essential polyunsaturated FA (PUFA) and their long-chain derivatives (LC-PUFA) are central nutrients required for cell membrane structure and bioactive molecule synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the pregnancy and/or lactation period, diet represents one of the essential environmental factors that can have beneficial or adverse consequences on phenotype and health of offspring [1]. Evidence that the quantity but also the type of dietary fatty acids (FA) in maternal diet during this period could influence the fetal programming has emerged [3][4][5]. Essential polyunsaturated FA (PUFA) and their long-chain derivatives (LC-PUFA) are central nutrients required for cell membrane structure and bioactive molecule synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Because fetus and newborn have a limited capacity to synthesize LC-PUFA, their intake mainly depends on the maternal availability and hepatic conversion from precursors. Several reports suggested that maternal LC-PUFA precursor's intake during the early stages of fetal development can influence lipid metabolism and signaling pathways leading to the development of later disorders in offspring [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odontogenesis is characterized by the following stages: dental lamina, button, cap, bell, crown, and rizinogenesis phases [ 20 ]. The harmful effects of maternal consumption of SFAs and TFAs, especially when consumed during pregnancy and/or lactation, are already known [ 17 , 18 ]. Previous studies have shown that the increased consumption of SFAs can lead to an increase in the levels of glucose, insulin, leptin, TNF-α, MCP-1, IL-6, NF-κB, and activation of TLR4 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of 10 g of soybean oil to every 1 kg of diet, except for diet C, was made to meet the minimum requirement of essential FAs. The experimental design was established in previous studies conducted by our group [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%